Expression of multidrug resistance proteins in invasive ductal carcinoma of the breast - LI, WEIQUAN (D.A. Spandidos, 2014)
Chemotherapy is commonly used for the treatment of breast cancer. However, the resistance to chemotherapeutic agents, often mediated by multidrug resistance (MDR) mechanisms, is a common occurrence. The present study examined the expression of several MDR-related proteins (MRPs) in invasive ductal carcinoma (IDC) of the breast, and assessed their association with clinicopathological variables and their prognostic significance. In addition, immunohistochemistry was used to measure the expression of MRP, p-glycoprotein (P-gp), topoisomerase 2α (Topo2α), thymidylate synthase (TS) and glutathione-S-transferase π (GST-π) in 156 resected IDCs of the breast. Pearson’s χ(2) test and Spearman’s correlation coefficient were used to analyze the association between MDR protein expression and several clinicopathological variables. The association between each of the five MDR proteins was also examined. Furthermore, Kaplan-Meier analysis and Cox regression modeling were used to assess overall survival. The expression of MRP, P-gp, Topo2α, TS and GST-π was detected in 20.5% (32/156), 25.0% (39/156), 84.0% (131/156), 41.7% (65/156) and 41.0% (64/156) of cases examined, respectively. No correlation was identified between MRP and Topo-2α and the clinicopathological variables examined. By contrast, P-gp (χ(2)=20.226; P<0.0001) and GST-π (χ(2)=35.032; P<0.0001) were found to positively correlate with tumor grade. In addition, staining for TS was associated with axillary lymph node metastasis (χ(2)=42.281; P<0.0001). The expression levels of P-gp and GST-π were found to be significantly correlated (r= 0.319; P<0.0001). Furthermore, GST-π expression was elevated in estrogen receptor-negative breast cancer (χ(2)=17.407; P<0.0001). Tumor histological grade, in addition to TS and GST-π expression, were significant predictors of a poor survival outcome. TS and GST-π are consequently useful prognostic biomarkers in IDC, therefore, when establishing a personalized chemotherapeutic plan, the expression of MDR proteins must be considered.